Certification of the Rough Resonance by the Wave Site of Matter for Welter Point on the Alteration Recognition System - lae Kim, Jeong; dong Kim, Kyu (International Journal of Engineering and Technology, 2018)
Wave alteration technology is formatted the resonance status for point-star pattern of the sparkle recognition rate (SRR) and vacuum recognition rate (VRR) on the wave recognition gestalt. The recognition rate condition by the wave recognition gestalt is associated with the welter resonance system. As to investigate a point-star pattern of the rough alteration, we are formatted of the wave value with wave layer point by the welter-down structure. The concept of recognition rate is made sure of the reference of sparkle rate and vacuum rate for alteration signal by the wave resonance gestalt. Moreover to appear a rough alteration of the SRR-VRR of the medium in terms of the wave-resonance gestalt, and wave point resonance that is gained the a wave value of the far alteration of the Wa-rm-FA-σMEX-MED with 12.03±2.28 units, that was the a wave value of the convenient alteration of the Wa-rm-CO-σMEX-MED with 2.71±0.51 units, that was the a wave value of the flank alteration of the Wa-rm-FL-σMEX-MED with 1.41±0.19 units, that was the a wave value of the vicinage alteration of the Wa-rm-VI-σMEX-MED with 0.22±0.10 units. The welter resonance will be to assess at the ability of the wave-resonance gestalt for the control degree recognition rate on the SRR-VRR that is clarified the rough sparkle and vacuum gestalt by the recognition rate system. Welter recognition system will be conjecture of a gestalt by the special signal and to count a wave data of welter resonance rate.